2015
DOI: 10.1007/s12609-014-0178-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-Infiltrating Lymphocytes (TILs) in Breast Cancer: a Predictive or a Prognostic Marker?

Abstract: Breast cancer has not been considered as an immunogenic solid cancer type; however, recent studies demonstrate evidence of significant prognostic information that can be derived from immune cell infiltration via tumourinfiltrating lymphocytes (TILs) in patient tumours. The presence of TILs has been associated with increased response rates to cytotoxic chemotherapy as well as targeted therapies, leading to improved disease-free and overall survival in certain breast cancer subtypes. Accordingly, experts have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 97 publications
1
2
0
Order By: Relevance
“…Interestingly, when stratified based on the presence of CD8+ lymphocytes, a high infiltration of FOXP3+ cells trended towards reduced survival in TNBC patients with low numbers of CD8+ cells. These results suggest that CD8+ lymphocytes could be the main effectors of anti-tumor immune responses, and that the consistent correlation between FOXP3 positivity and cytotoxic lymphocytes may in part explain conflicting results reported in previous studies [8]. …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Interestingly, when stratified based on the presence of CD8+ lymphocytes, a high infiltration of FOXP3+ cells trended towards reduced survival in TNBC patients with low numbers of CD8+ cells. These results suggest that CD8+ lymphocytes could be the main effectors of anti-tumor immune responses, and that the consistent correlation between FOXP3 positivity and cytotoxic lymphocytes may in part explain conflicting results reported in previous studies [8]. …”
Section: Discussionsupporting
confidence: 57%
“…However, the composition of the tumor immune microenvironment is very heterogeneous, and the functional significance of specific immune cell subpopulations remains poorly understood. Indeed, cytotoxic CD8+ T cells have been shown to be an independent favorable prognostic factor, while studies on CD4+ T helper and forkhead box protein 3 (FOXP3) + T regulatory cells have shown conflicting results [8]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, low density of CD3+, CD4+, and CD8+ cells may increase the risk of relapse in squamous cell cervical cancer (Nedergaard et al, 2007). Further, higher numbers of CD3+, CD4+, and CD8+ tumor-infiltrating lymphocytes (TILs) is a predictor of extended survival in patients with infiltrating ductal carcinoma of the breast (Dushyanthen et al, 2015). In this study, the expression of CD3+ and CD4+ was correlated to tumor infiltration and metastasis.…”
Section: Discussionmentioning
confidence: 70%